2012
DOI: 10.3109/13813455.2012.735245
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of fasting total homocysteine, high sensitivity C-reactive protein and features of the metabolic syndrome in Trinidadian subjects

Abstract: Serum C-reactive protein is significantly related to features of the metabolic syndrome. Total plasma homocysteine, appears to be independent of both hs-CRP and features of the metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Associated lipid / lipoprotein abnormalities include reductions in high density lipoprotein (HDL) cholesterol and increased total cholesterol, LDL and triglyceride levels [8]. Some, but not all studies, reported increased homocysteine levels in the metabolic syndrome [11], and homocysteine is a putative biomarker for depression and bipolar disorder [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Associated lipid / lipoprotein abnormalities include reductions in high density lipoprotein (HDL) cholesterol and increased total cholesterol, LDL and triglyceride levels [8]. Some, but not all studies, reported increased homocysteine levels in the metabolic syndrome [11], and homocysteine is a putative biomarker for depression and bipolar disorder [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 66 articles were included, including 9 cohort studies, 48 cross-sectional studies, and 13 case-controls. As four articles ( 41 , 51 , 60 , 68 ) had analyzed the association in two different groups of participants each, a total of 70 records were included. The geographic distribution was as follows: China (11 articles), South Korea (9 articles), Turkey (7 articles), United States (6 articles), Italy (3 articles), Iran (3 articles), India (3 articles), Serbia (2 articles), Bangladesh (2 articles), France (2 articles), Saudi Arabia (2 articles), Spain (1 article), Ecuador (1 article), Netherlands (1 article), Canada (1 article), Taiwan (1 article), Australia (1 article), Romania (1 article), Trinidad & Tobago (1 article), Nigeria (1 article), Poland (1 article), Greece (1 article), South Africa (1 article), Slovenia (1 article), Cameroon (1 article), Peru (1 article), and multiple Mesoamerican countries (1 article).…”
Section: Resultsmentioning
confidence: 99%